Response of Rice (Oryza sativa L) to Split Application of Potassium in Old Brahmaputra Flood Plain Soil (Bangladesh Journal of Agricultural Research, 2012)
Not available DOI: http://dx.doi.org/10.3329/bjar.v37i1.11192 Bangladesh J. Agril. Res. 37(1): 179-184, March 2012